2013
DOI: 10.1007/s11357-013-9530-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased fruit and vegetable consumption on physical function and muscle strength in older adults

Abstract: Fruit and vegetable (FV) intake, which is often low in older people, may be associated with improved muscle strength and physical function. However, there is a shortage of intervention trial evidence to support this. The current study examined the effect of increased FV consumption on measures of muscle strength and physical function among healthy, free-living older adults. A randomized controlled intervention study was undertaken. Eightythree participants aged 65-85 years, habitually consuming ≤2 portions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 43 publications
6
47
2
Order By: Relevance
“…There were no studies in children that passed the inclusion and exclusion criteria. Two studies met all criteria (28, 31) (primary analysis), and 5 other studies met all criteria except for not explicitly stating weight was an a priori outcome of interest [secondary analysis 2 7 studies total; an additional 5 studies (27,28,(32)(33)(34) were combined with the 2 studies in the primary analysis group]. We included the second group in the secondary analysis because weight outcomes were reported or data were provided on request in a usable form.…”
Section: Results Of Study Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no studies in children that passed the inclusion and exclusion criteria. Two studies met all criteria (28, 31) (primary analysis), and 5 other studies met all criteria except for not explicitly stating weight was an a priori outcome of interest [secondary analysis 2 7 studies total; an additional 5 studies (27,28,(32)(33)(34) were combined with the 2 studies in the primary analysis group]. We included the second group in the secondary analysis because weight outcomes were reported or data were provided on request in a usable form.…”
Section: Results Of Study Search and Selectionmentioning
confidence: 99%
“…Bradbury et al (32) created modified recipes for denture wearers, such as focusing on F/V recipes that were seed free. Wagner (31) focused intake assessments on F/Vs that were high in antioxidants, whereas Neville et al (34) purchased and supplied foods that participants indicated that they liked with "no prescriptive list offered to participants at any point. "…”
Section: General Comparison Of Included Studiesmentioning
confidence: 99%
“…Similarly, another study where aged rats were given either 10 or 50 % Concord grape juice for 8 weeks reported a significant improvement in motor function only in the 50 % Concord grape juice group when compared to the controls . In spite of evidence supporting beneficial effects of fruits and vegetables on motor function Shukitt-Hale et al 2005;Galli et al 2006;Neville et al 2013;Shukitt-Hale et al 2015), this null effect of tart cherry on motor function is supported by several studies where diets high in antioxidant capacity or fruits high in polyphenolic compounds fail to reverse agerelated motor deficits in spite of other health benefits Sumien et al 2004;ShukittHale et al 2005). Because age-related motor deficits begin to manifest during early middle-age in rodents (Shukitt-Hale et al 1998;de Fiebre et al 2006) and deteriorate profoundly with age , it is possible that age-related damage may be too widespread by the time of late-life intervention, making it difficult to reverse (Bickford 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study from Hong Kong (n = 3957) found that the dietary pattern "vegetables-fruits" was associated with lower odds for sarcopenia in men aged ≥65 years cross-sectionally [18]. Finally, a small randomized controlled trial conducted in the UK found a trend towards greater increase in grip strength in the group that consumed higher portions of fruits and vegetables [19].…”
Section: Introductionmentioning
confidence: 99%